Numerical modeling of the transient dynamics of a skier while gliding - Roberts, C. C. (1987)
Calculating the speed of a skier performing a straight run (skiing straight down the hill with skis not edged) is of interest to ski areas designers, ski equipment designers, ski areas and ski accident reconstructionists. A mathematical model is developed utilizing the balance between aerodynamic, frictional and gravitational forces. Aerodynamical forces are calculated using classical incompressible flow theory with input parameters such as air density, drag coefficient and profile of the skiers stance. Frictional resistances are obtained from data on the profile of the hill. The computation is performed in closed form in concert with the finite difference method. The speed of the skier is calculated at various distances on various slopes. Calculations are compared with actual skier runs.